2015
DOI: 10.1124/dmd.115.065276
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Large Intestine in Regulating Bile Acids and Glucagon-Like Peptide-1 in Germ-Free Mice

Abstract: It is known that 1) elevated serum bile acids (BAs) are associated with decreased body weight, 2) elevated glucagon-like peptide-1 (GLP-1) levels can decrease body weight, and 3) germ-free (GF) mice are resistant to diet-induced obesity. The purpose of this study was to test the hypothesis that a lack of intestinal microbiota results in more BAs in the body, resulting in increased BA-mediated transmembrane G protein-coupled receptor 5 (TGR5) signaling and increased serum GLP-1 as a mechanism of resistance of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 57 publications
6
58
0
1
Order By: Relevance
“…Perturbation of intestinal bacteria affects the ratio of conjugated and unconjugated BAs and the ratio of primary and secondary BA, which have differential effects on BA receptors. As expected, an altered BA profile has been observed in gnotobiotic animals (37, 38). …”
Section: Gut Bacterial Metabolites Co-metabolites and Other MIsupporting
confidence: 83%
“…Perturbation of intestinal bacteria affects the ratio of conjugated and unconjugated BAs and the ratio of primary and secondary BA, which have differential effects on BA receptors. As expected, an altered BA profile has been observed in gnotobiotic animals (37, 38). …”
Section: Gut Bacterial Metabolites Co-metabolites and Other MIsupporting
confidence: 83%
“…Previous studies have shown that in mice, colonization with gut bacteria can directly regulate signaling of the FXR in the gut and, in this manner, modify bile acid metabolism and potentially lipid and glucose homeostasis (Sayin et al, 2013). In this issue, Selwyn et al (2015a) provide evidence that the gut microbiome may contribute to the generation of bile acids that are capable of acting as agonists of TGR5 in concentrations sufficient for increasing ileac secretion of the TGR5 target, GLP-1.…”
Section: Role Of the Gut Microbiota In Bile Acid Metabolismmentioning
confidence: 85%
“…In humans, UDCA is a secondary bile acid, and MCAs are generally not detected. We and others have shown that in the absence of bacteria (as in GF or antibiotic-treated mice or rats), the bile acid pool consists of mainly primary conjugated bile acids (Kellogg et al, 1970;Kellogg and Wostmann, 1969;Koopman et al, 1986;Sayin et al, 2013;Selwyn et al, 2015;Wostmann, 1973). Early experiments in GF rats indicated that MCAs are synthesized in the liver from CDCA (Gustafsson et al, 1981); however, the enzyme(s) involved in this process are still not defined.…”
Section: Microbial Regulation Of Bile Acid Synthesismentioning
confidence: 93%
“…A minor part of deconjugated secondary bile acids is also absorbed from the gut through passive diffusion and gets enriched in the enterohepatic circulation and may then act as signaling molecules in the host. Levels of uMCA, MDCA, and HDCA detected in the feces of mice can vary substantially among different mouse facilities (Degirolamo et al, 2014;Sayin et al, 2013;Selwyn et al, 2015), and this could be attributed to differences in gut microbiota composition that shifts the microbial modification of the bile acids. Importantly, it has been suggested that the human gut microbiota is unable to metabolize bMCA (Martin et al, 2007(Martin et al, , 2008Sacquet et al, 1984Sacquet et al, , 1985.…”
Section: Microbial Metabolism Of Bile Acidsmentioning
confidence: 96%